The Tribulations of Polish Judges (2015–2023) or the Sally-Anne Test of Judicial Independence - Kubas, Sebastian (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The issue of judicial independence in Poland has deservedly attracted attention in academic circles in recent years. In this article, I address this issue by examining how the stress test of constitutional democracy proceeded within the Polish judiciary. I argue that developments in Poland exposed weakness in an important constitutional doctrine of judicial independence. Therefore, I seek to complicate the picture by bringing to light some older developments, pre-2015, but also by referring to a psychological experiment dealing with false beliefs (the Sally-Anne test). This article is an attempt to show what lessons can be drawn from Poland’s democratic backsliding, focusing particularly on why the issue of judicial independence failed to generate electoral change after 2015 and how the legalists’ reliance on legal proceedings proved ineffective. The concept of constitutional fracking is introduced to show how the Polish Allied Right ruling bloc exploited inconsistencies in the concept of judicial independence.